2016
DOI: 10.1002/ente.201600360
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Graphite Anodes with Lithium Sulfate to Improve the Cycle Performance of Lithium‐Ion Batteries

Abstract: Graphite electrode surfaces are pretreated by spray‐deposition method with 0.5 mol L−1 Li2SO4 aqueous solution. The physical and electrochemical properties of a solid electrolyte interphase (SEI) film formed on the surface of Li2SO4‐treated graphite electrode are investigated by Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy, and electrochemical measurements. The results show that the SEI film formed, promoted by Li2SO4, is thin, stable, effective, and elastic to accommodate volume c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…4b and 4c, the SEI film resistance (R F ) and SEI film capacitance (C F ) at LCVs of 3.47, 3.00, and 2.50 V are identical; each R F gradually decreases up to 50 cycles and then remains constant in the following cycles, while C F gradually increases up to 50 cycles and then remains constant. These trends are similar to the results observed in our previous study where charge-discharge cycling was performed in the voltage ranges of 3.47-4.20 V and 3.47-4.40 V. 2 Cui et al 22 reported that an initial drop in R F is due to the continuous formation/modification of the primary rough SEI film. The SEI film is composed of organic and inorganic components.…”
Section: Resultssupporting
confidence: 90%
“…4b and 4c, the SEI film resistance (R F ) and SEI film capacitance (C F ) at LCVs of 3.47, 3.00, and 2.50 V are identical; each R F gradually decreases up to 50 cycles and then remains constant in the following cycles, while C F gradually increases up to 50 cycles and then remains constant. These trends are similar to the results observed in our previous study where charge-discharge cycling was performed in the voltage ranges of 3.47-4.20 V and 3.47-4.40 V. 2 Cui et al 22 reported that an initial drop in R F is due to the continuous formation/modification of the primary rough SEI film. The SEI film is composed of organic and inorganic components.…”
Section: Resultssupporting
confidence: 90%
“…Reports show that Li 2 SO 4 -treated graphite exhibits outstanding cycling performance and low interfacial impedance. 9 Therefore, the formation of Li 2 SO 4 -dominating SEI using DTD is an effective method to improve the performance of graphite anode.…”
Section: Resultsmentioning
confidence: 99%
“…Cui et al used a surface treatment of Gr with 0.5 mol L À1 Li 2 SO 4 aqueous solution, which resulted in the formation of thinner, more stable and elastic SEI layer capable of accommodating structural changes during cycling. 233 The study suggests that surface properties play an important role in the formation process. Further studies have found a correlation between Gr surface properties and first cycle specific charge loss, confirming the importance of the surface properties of active material.…”
Section: Materials and Cell Designmentioning
confidence: 98%